Simultaneous C5 and CD14 inhibition limits inflammation and organ dysfunction in pig polytrauma - Lupu, Ludmila; Horst, Klemens; Greven, Johannes; Mert, Ümit; Ludviksen, Judith A.K.; Pettersen, Kristin; Lau, Corinna; Li, Yang; Palmer, Annette; Qin, Kang; Zhang, Xing; Mayer, Benjamin; et al. (Frontiers in Immunology, 2022)
Dysfunctional complement activation and Toll-like receptor signaling immediately after trauma are associated with development of trauma-induced coagulopathy and multiple organ dysfunction syndrome. We assessed the efficacy of the combined inhibition therapy of complement factor C5 and the TLR co-receptor CD14 on thrombo-inflammation and organ damage in an exploratory 72-h polytrauma porcine model, conducted under standard surgical and intensive care management procedures. Twelve male pigs were subjected to polytrauma, followed by resuscitation (ATLS® guidelines) and operation of the femur fracture (intramedullary nailing technique). The pigs were allocated to combined C5 and CD14 inhibition therapy group (n=4) and control group (n=8). The therapy group received intravenously C5 inhibitor (RA101295) and anti-CD14 antibody (rMil2) 30 min post-trauma. Controls received saline. Combined C5 and CD14 inhibition reduced the blood levels of the terminal complement complex (TCC) by 70% (p=0.004), CRP by 28% (p=0.004), and IL-6 by 52% (p=0.048). The inhibition therapy prevented the platelet consumption by 18% and TAT formation by 77% (p=0.008). Moreover, the norepinephrine requirements in the treated group were reduced by 88%. The inhibition therapy limited the organ damage, thereby reducing the blood lipase values by 50% (p=0.028), LDH by 30% (p=0.004), AST by 33%, and NGAL by 30%. Immunofluorescent analysis of the lung tissue revealed C5b-9 deposition on blood vessels in five from the untreated, and in none of the treated animals. In kidney and liver the C5b-9 deposition was similarly detected mainly the untreated as compared to the treated animals. Combined C5 and CD14 inhibition limited the inflammatory response, the organ damage, and reduced the catecholamine requirements after experimental polytrauma and might be a promising therapeutic approach.